Investing in Women’s Employment : Good for Business, Good for Development - International Finance Corporation (Washington, DC, 2013)
Economic growth is more robust and sustainable when women and men alike participate fully in the labor market. Better jobs for women, employment that leads to higher wages and greater decision-making, also have a positive influence on the ways households spend money on children s nutrition, health, and education. Meanwhile, companies that invest in women s employment gain an important competitive advantage. Yet despite the persuasive evidence that gender equality has a transformative effect on productivity and growth, women s full economic and productive potential remains unrealized in many parts of the world. Globally, while women s education levels have increased and educated women now earn more than their uneducated peers, gender gaps in labor-market participation and wage levels persist. Women continue to be underrepresented in formal and higher value-added employment. This report, investing in women s employment: good for Business, good for development, is the first result of the WINvest initiative. It draws on members experiences and encourages business to tap and manage female talent in emerging and developing markets.